Analisis Kepuasan Kerja dan Kinerja Perawat Terhadap Kualitas Pelayanan di Rumah Sakit Pusdikkes Jakarta Timur - Elfrida Novita Savitri; Budiharto Budiharto; Samingan Samingan (LPPM Universitas Respati Indonesia, 2026)
The quality of hospital services is influenced by various factors, one of which is the performance and job satisfaction of nurses, who represent the largest group of healthcare professionals and play a direct role in delivering patient care. At Rumah Sakit Pusdikkes, East Jakarta, a decline in patient satisfaction with nursing services has been identified, which is suspected to be related to nurses’ job satisfaction and performance. This study aims to analyze the impact of job satisfaction and nurse performance on the quality of healthcare services at RS Pusdikkes East Jakarta. This study employed a quantitative research method with a cross-sectional design. The study population consisted of all 78 staff nurses at RS Pusdikkes, all of whom were included as the sample using a total sampling technique. Data were collected using a Likert scale–based questionnaire that had undergone validity and reliability testing. Data analysis was carried out through several methods, including univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis through logistic regression. The results showed that most nurses had high levels of job satisfaction and performance. There was a significant relationship between job satisfaction and service quality (p = 0.004), as well as between nurse performance and service quality (p = 0.001). Multivariate analysis revealed that nurse performance was the most influential factor, with an odds ratio of 31.8 in affecting service quality (p = 0.000), while job satisfaction (p = 0.620) did not have a significant effect when nurse performance was taken into account. Based on these findings, it can be concluded that job satisfaction and nurse performance jointly contribute to service quality. Therefore, managerial efforts should focus on improving nurses’ well-being and systematically evaluating their performance to ensure optimal healthcare service quality